Influence mechanism of cooling time on the shutdown purge process in proton exchange membrane fuel cells - Yang Chao; Houyu Wei; Zhenya Zhang; Xuewei Li; Jiean Tian (Case Studies in Thermal Engineering)
This study investigates the impact of cooling duration on the shutdown purge process through integrated water and thermal management in fuel cells. Using a comprehensive stack testing platform, experimental studies were conducted at a purge temperature of 338.15 K. The experimental results demonstrate a significant increase in the high-frequency resistance within the cell after purge completion, with its rise accelerating as the thermostat opening increases. Furthermore, a simulation model was used to analyze changes in internal moisture content during a 180-s purge process under different cooling durations. The research reveals that while purge performance improves with extended cooling time, this improvement gradually diminishes when the cooling duration exceeds 90 s. Detailed analysis indicates that when the cooling time surpasses 150 s, there is a substantial reduction in residual membrane water content after 180 s of purging, along with a notable decrease in the time required for complete removal of liquid water from porous media. Considering practical system operation, economics, and safety, a cooling duration of 150 s is recommended. This optimized thermal control strategy provides crucial technical support for enhancing fuel cell performance and durability.